ANALYSIS OF FINANCIAL STATEMENTS TO ASSESS THE FINANCIAL PERFORMANCE OF PT. ARGO PANTES TBK PERIOD 2017-2021 - Nurlela; Laelis Neni; Wawan Iswanto (Jurnal Ekonomi, 2022)
The purpose of the study was to determine the financial performance of PT Argo Pantes Tbk during the 2017-2021 period through financial statement analysis using financial ratios of liquidity, profitability, activity and solvency. In order to find out the cause of the decline in the company's equity and assets. The type of research data used is secondary data collected by documentation techniques and literature study. The data analysis method used is descriptive quantitative. Based on the results of the study, it is known that the financial performance of PT. Agro Pantes Tbk is classified as bad because the company's financial condition is in the unhealthy category. This situation is seen from the value of the ratio of liquidity, profitability, activity and solvency which is still below the industry average from 2017-2021.